2022
DOI: 10.1155/2022/6840716
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasonography-Guided Combination with Elbow Arthrography-Assisted Minimally Invasive Treatment of Radial Neck Fractures in Young Children

Abstract: Background. A radius neck fracture in children is a common fracture that not only affects the growth and development of children but also has a certain impact on the function of children’s elbow joints. Objective. To probe into the application value of ultrasonography- (US-) guided combination with elbow arthrography in the minimally invasive treatment of radial neck fractures in young children, summarize its clinical effect and provide a minimally invasive, safe, effective, and reliable method for treating ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…The fracture fragment may not be visible in the lateral film due to the shielding of the proximal part of the ulna, or an overlapping image of the fracture can be vaguely seen. [ 6 , 7 ] If the patient is rejected to rotate the swollen forearm, ultrasound is a suitable evaluation tool to avoid misdiagnosis (Fig. 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fracture fragment may not be visible in the lateral film due to the shielding of the proximal part of the ulna, or an overlapping image of the fracture can be vaguely seen. [ 6 , 7 ] If the patient is rejected to rotate the swollen forearm, ultrasound is a suitable evaluation tool to avoid misdiagnosis (Fig. 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…[4] The ultrasound or magnetic resonance imaging were also advised to confirm diagnoses. [5][6][7][8] Due to the high miss-diagnose rate in TRASH preschool patients (TRASH-PS), we reviewed the meaningful use of ultrasound of TRASH-PS fractures.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Additionally, several studies have confirmed the utility of ultrasound in assessing reduction adequacy. [13,14] In literature, some studies [15][16][17] have shown that ultrasound-guided diagnosis is reliable in detecting fractures of RNFs. Nevertheless, to our knowledge, we know of no previous studies reported in the literature comparing 2 different ultrasonography (US)-guided closed reduction and fixation methods in managing displaced radial neck fractures in children.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%